Fat Emulsion Intragastric Stability and Droplet Size Modulate Gastrointestinal Responses and Subsequent Food Intake in Young Adults. Issue 6 (29th April 2015) - Hussein, Mahamoud O; Hoad, Caroline L; Wright, Jeff; Singh, Gulzar; Stephenson, Mary C; Cox, Eleanor F; Placidi, Elisa; Pritchard, Susan E; Costigan, Carolyn; Ribeiro, Henelyta; Ciampi, Elisabetta; Nandi, Asish; et al.
Abstract: Background: Intragastric creaming and droplet size of fat emulsions may affect intragastric behavior and gastrointestinal and satiety responses. Objectives: We tested the hypotheses that gastrointestinal physiologic responses and satiety will be increased by an increase in intragastric stability and by a decrease in fat droplet size of a fat emulsion. Methods: This was a double-blind, randomized crossover study in 11 healthy persons [8 men and 3 women, aged 24 ± 1 y; body mass index (in kg/m 2 ): 24.4 ± 0.9] who consumed meals containing 300-g 20% oil and water emulsion (2220 kJ) with 1 ) larger, 6-μm mean droplet size (Coarse treatment) expected to cream in the stomach; 2 ) larger, 6-μm mean droplet size with 0.5% locust bean gum (LBG; Coarse+LBG treatment) to prevent creaming; or 3 ) smaller, 0.4-μm mean droplet size with LBG (Fine+LBG treatment). The participants were imaged hourly by using MRI and food intake was assessed by using a meal that participants consumed ad libitum. Results: The Coarse+LBG treatment (preventing creaming in the stomach) slowed gastric emptying, resulting in 12% higher gastric volume over time ( P < 0.001), increased small bowel water content (SBWC) by 11% ( P < 0.01), slowed appearance of the 13 C label in the breath by 17% ( P < 0.01), and reduced food intake by 9% ( P < 0.05) compared with the Coarse treatment. The Fine+LBG treatment (smaller droplet size) slowed gastric emptying, resulting in 18% higher gastric volume ( P < 0.001), increased SBWC content by 15% ( P < 0.01), and significantly reduced food intake by 11% ( P < 0.05, equivalent to an average of 411 kJ less energy consumed) compared with the Coarse+LBG treatment. These high-fat meals stimulated substantial increases in SBWC, which increased to a peak at 4 h at 568 mL (range: 150–854 mL; P < 0.01) for the Fine+LBG treatment. Conclusion: Manipulating intragastric stability and fat emulsion droplet size can influence human gastrointestinal physiology and food intake.